Real‐World Experience With Emicizumab for Haemophilia A From the Physician Perspective in a Real‐World Clinical Setting - Michael Recht; Chris Blazos; Sophie Lai; Nathan Ball; Ella Morton; Lucy Lee; Juliana M. L. Biondo; Janet S. Lee (Haemophilia, 2026)
ABSTRACT Introduction Emicizumab is a bispecific antibody approved for prophylaxis in people with haemophilia A (PwHA). Aim To describe from the physician perspective the characteristics and treatment experiences of PwHA receiving emicizumab. Methods The Adelphi Real World Haemophilia Disease Specific Programme is a cross‐sectional, retrospective data collection from US haematology and haematology‐oncology specialists between July 2023 and April 2024. Male PwHA with or without inhibitors were included if they had baseline factor VIII levels 80% of the prescribed dose. More PwHA had zero treated bleeds (76.9% vs. 42.9%), with fewer bleeding events (mean [SD], 1.3 [1.9] vs. 0.4 [1.1]; p = 0.0001) during the post‐emicizumab period (median [IQR] follow‐up, 12.0 [1.3–12.0] months) than in the 12 months pre‐emicizumab. Post‐emicizumab outcomes were similarly improved across settings, whether at federally funded HTCs or elsewhere. Conclusion Among PwHA receiving emicizumab, rates and severity of bleeds decreased after emicizumab initiation, regardless of the clinical setting.